Penerapan Cloud Computing Pada Sistem Reservasi Homestay Dieng Berbasis Web - Rusydi Umar, Alan Fajar Sudrajat (Program Studi Sistem Informasi, 2017)
Homestay is one of the places needed as lodging facilities in the tourist area. In recent years, lodging business is greatly increasing. Business lodging in Dieng is one of the promising venture business' due to the increasing number of the tourists who interested to visit the tourist places in Dieng and they need the hotel services. However, there are some managers who are unable to promote their lodging through the internet. Therefore, this research will make a software as a service in a cloud computing, regarding the Homestay Reservation System service in order to make the managers able to promote their homestay to public through the internet and it will make customers able to make a reservation through the software. This software was made by following waterfall paradigm in software engineering, start from analysis, design, implementation and testing. Testing result showed that the application deserved to be used.Keywords: information, cloud computing, homestay, reservation